IMPLATED OF COVERED BILIARY PROSTHESES THROUGH ULTRASOUND-GUIDED ACCESS: PRELIMINARY RESULTS AND REVIEW OF THE LITERATURE - Anna Castaldo (Euromediterranean biomedical journal, 2022)
The purpose of the study is to describe the percutaneous management and the safety and efficacy results of the implantation of covered biliary stents positioned in the main biliary tract in patients suffering from obstructive hyperbilirubinemia caused by unresectable neoplasms. We also performed a comparison between the procedural data of right or left percutaneous hepatic access. A monocentric retrospective study was performed from January 2015 to August 2020, in which we examined 27 patients who had severe hyperbilirubinemia (values > 7 mg / dL) and unresectable neoplasms with indication for palliative therapy. The treatment was performed through an interventional radiology procedure. The technical success was considered as release of the covered prosthesis. Therapeutic success was considered as patency of the metal prosthesis through reduction in bilirubin by > 4 mg / dL and the frequency of cholangitis episodes in the follow-up of the study. Overall, 7 of the 27 procedures performed from January 2015 to August 2020 were included in the study. In 2 of the 7 patients there was a microperforation of the biliary tract with spread of contrast medium. In all cases, the technical success of the procedure was observed. There were no statistically significant differences between the results of accesses from the right and left lobe. Our study suggests that the interventional radiology procedure is a safe and effective procedure. The study is limited by the small number of patients studied and needs further studies.